Column study for the Cu(II) removal by the coconut shell from aqueous solution – MLR and GA modeling - Sarkar, Shreyashi; Bar, Nirjhar; Das, Sudip Kumar (Journal of Environmental Engineering and Landscape Management, 2022)
Adsorption characteristics of locally available inexpensive natural adsorbent coconut shells were studied for Cu(II) removal. The present study adsorption process was carried through a fixed bed column to find out the breakthrough characteristics. The variation of operating variables is investigated, pH 6, influence Cu(II) concentration (10–30 mg·L–1), bed height (5–15 cm), the flow rate (10–30 ml·min–1). The suitability of various kinetic models has been tested. Maximum adsorption capacity, qe according to Thomas model, was 30.09 mg·g–1obtained at 20 ml/min, flow rate, 30 mg·L–1 metal solution, and 15 cm bed height. The correlation coefficient of the Thomas model ranges from 0.8260 to 0.9839. Besides this, according to the statistical parameters of the Yoon-Nelson and Yan et al. models, proving that the experimental data are suitable for this model. The statistical and GA modeling of the experimental data has also been performed successfully.